The Insurrection of Eros: about the ruin of negative capacity in contemporary culture (Research, Society and Development, 2021)
This work develops a reflection about contemporary culture and current ways of life, discussing some of the logics that not only organize present times, but also that make possible a series of problems of psychosocial nature. It is a qualitative research presented in the form of a theoretical essay that analyzes a culture marked by the impact of the current forms of capitalism on its neoliberal front. In such culture, there is a considerable praise of happiness, of pleasure, of consumerism and of productivity, in order that which escapes the time of capitalism – such as suffering and as negative capability – ceases to be valued and is purged at any price. In this time that postulates happiness as a duty and an imperative, important aspects of existence are disregarded in favor of motions that enclose life in logics of alleged economic development. Thereby it is considered the relevance of culturally neglected elements such as negative capability and suffering as possible tools in the articulation of resistances in face of cultural impositions which crystallize the ways of being in the world.